Intelligent Car Park System - Saw, Qher Shynn (Universiti Sains Malaysia, 2005)
The main objective of this project is to design an intelligent car park system based on computer and Micro controller. This prototype is build using a model to stimulate the actual car park system. High-level language such as Visual Basic 6 is chosen because it can be used to build a convenient system. By using Visual Basic 6, a user-friendly Graphic User Interface can be created. The basic concept of this project is similar to that of a normal car park, but it has been enhanced with various useful features such as number of cars enters, number of cars illegally parked and number of available lots. All signals will be first processed by the PIC16F877A micro controller and then sent by it to the computer. The main hardware consists of a PIC16F877A micro controller by Microchip Technology Inc, LDR sensors and 7404 Hex Inverter ICs. LDR sensors are placed at entrance and every parking lot to detect cars. The source code of the PIC micro controller is developed using MPLAB Integrated Development Environments while the interface of the car park system is created using Microsoft Visual Basic 6. The main advantages of this project are information is carried out from time to time to give a clear view of empty lots available for drivers. Time consuming can be reduced to the lowest level. Besides that, the cost required to build and manage this intelligent car park system is low so that any company or shopping centre able to possess. Any inconvenience during finding parking lot can be solved easily. This project also designs for capable of guardhouse monitoring activities inside the car park.